The relationship between university student help-seeking intentions and well-being outcomes - McCabe, Melinda; Byrne, Michelle; Gullifer, Judith; Cornish, Kim (Frontiers in Psychiatry, 2024)
University represents a time of both great uncertainty and change as well as a time of opportunity and learning. University students represent a population both at a higher risk of experiencing poor mental health and diagnosis, and a population with relatively greater access and communication of both mental health literacy resources and mental health support services. Despite this we consistently see low intention of help seeking for mental health services or health services, with a clear preference shown for personal contacts such as friends or parents. To understand help seeking intentions and their relationship with wellbeing, the current study explored two core hypotheses, when assessing a broad range of help seeking options, the likelihood of seeking support from a range of sources will cluster together to create help seeking groupings that can be further explored (1) and that across these help seeking factors there would be difference in intention score across students who fall within 'atrisk', 'low', or 'normal to high' wellbeing groupings (2). Through a series of exploratory factor analysis on a subsample (N=178) and final confirmatory factor analysis (N=1597) identified 5 help seeking factors: Intimate Partner (single item), Personal Relations (friends, parents, and other relatives), External Health Service (external mental health provider and health provider) University Health Service (university mental health and health provider), and Digital and Distal Professional (digital apps, websites or forums, telehealth, religious leaders, and phone or online emergency services). To address hypothesis 2 a multivariate analysis of covariance was run to assess help seeking intentions across factors between students with 'at-risk' (N=453), 'low' (N=484), or 'normal to high' (N=563) wellbeing scores. Although significant differences were found between groups on almost all help seeking factors (except External Health Service) the differences between groups were small. However, consistently those with 'normal to high' wellbeing demonstrated higher intention to seek help compared to 'low' and 'at-risk' groups. Across all groups Personal Relations demonstrated the highest average help seeking intention score and, in addition to supporting findings in previous literature, represents a potential 'lowest hanging fruit' of help seeking source for university students.